A mass model for estimating the gamma ray background of the Burst and Transient Source Experiment - Shaw, S. E.; Westmore, M. J.; Bird, A. J.; Dean, A. J.; Ferguson, C.; Gurriaran, R.; Lockley, J. J.; Willis, D. R. (Astronomy and astrophysics (Berlin), 2003)
Orbiting X-ray and gamma ray instruments are subject to large background count rates due to local particle fluxes in the space environment. The ability of an instrument to make calibrated measurements of the flux from a source of interest is highly dependent on accurately determining the background level. We present here a method of calculating the energy dependent background flux for any point in the complete data set recorded by the Burst and Transient Source Experiment (BATSE) in its nine year mission. The BATSE Mass Model (BAMM) uses a Monte Carlo mass modelling approach to produce a data base of the gamma ray background which is then filtered to simulate the background count rate with a 2.048 s time resolution. This method is able to reduce the variations in the background flux by a factor of 8–10, effectively “flat-fielding” the detector response. With flat-fielded BATSE data it should be possible to use the Earth occultation technique to produce a hard X-ray all sky survey to the 1–2 mCrab sensitivity limit. BAMM is also capable of estimating the contribution to the spectra measured from gamma ray sources due to the reprocessing of source photons in inactive material surrounding a gamma ray detector. Possible applications of this aspect of the model in the area of Gamma Ray Burst spectral analysis are discussed.